Relationship Analysis between Environmental Sanitation and 3M Plus Behaviour as Determinants of DHF Incidence at Nagaswidak Health Center, Palembang - Putri, Dian Meiza; Fitriani, Dwi; Hasyim, Hamzah; Novitrie, Ayu; Windusari, Yuanita (Jurnal EnviScience (Environment Science), 2025)
Dengue hemorrhagic fever (DHF) remains a major public health concern in tropical regions, including Indonesia, with increasing incidence in urban communities. This study aimed to analyze the relationship between household environmental sanitation and 3M Plus preventive behavior with DHF incidence in the working area of Nagaswidak Health Center, Palembang. An analytical observational case–control study was conducted in 2025 involving 102 respondents (34 cases and 68 controls) selected purposively. Data were collected through structured interviews and direct environmental observation and analyzed using chi-square tests and multivariate logistic regression with a 95% confidence interval. Bivariate analysis showed significant associations for water container condition, waste disposal, residential density, cleaning behavior, mosquito repellent use, and abate application (p<0.05). Multivariate analysis identified poor waste disposal (OR=2.41; 95% CI: 1.08–5.37) and lack of abate application (OR=3.12; 95% CI: 1.29–7.51) as dominant factors associated with DHF incidence. Household environmental sanitation and selected 3M Plus behaviors contribute substantially to DHF occurrence. Strengthening routine abate distribution and improving community-based waste management should be prioritized to reduce dengue transmission risk in this endemic urban setting.